Ecological Features of Biogas Production - Meliyev Muzaffar Saidakbarovich; Axmadjonova Zulxumorxon Nazirjon qizi; Mo’vinova Shoiraxon Iqboljon qizi (International Journal on Orange Technologies, 2021)
This article is written about biogas production and its environmental characteristics, which is one of the ways of solving the energy problem, which is one of the problems of thermodynamics. The article also shows examples of the economic efficiency achieved due to the production of biogas in economically developed countries and their technologies